CLOUD COMPUTING SECURITY AND DATA PROTECTION: A REVIEW - Singh, Gurpreet; Mishra, Susmita (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Scientific computing in the 21st century has evolved from fixxed to distributed work environment. The current trend of Cloud Computing (CC) allows accessing business applications from anywhere just by connecting to the Internet. Evidence shows that, switching to CC organizations' annual expenditure and maintenance are being reduced to a greater extent. However, there are several challenges that come along with various benefits of cloud computing. Among these include security aspects. Our aim is to identify security challenges for adapting cloud computing and their solutions from real world for the challenge that do not have any proper mitigation strategies identified.This non-existence of global standards and guidelines could be help academics to know the state of practice and formulate better methods/standards to provide secure interoperability. The identified cloud computing security challenges and solutions, can be referred by practitioners to understand which areas of security need to be concentrated while adapting/migrating to a cloud computing environment.Â 